Anti-corrosion rubber material as well as preparation method and application thereof

By using uruolol acetal resin to modify EPDM rubber and other components, rubber materials with excellent anticorrosion and mechanical properties are prepared, which solves the problem of poor anticorrosion performance of existing rubber lining materials and achieves wider applications.

CN119613877APending Publication Date: 2025-03-14HEBEI XIANGYI MEDICAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411983731.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing rubber lining materials have poor corrosion resistance, resulting in limited application range.

Method used

Raw material components such as uruol acetal resin modified ethylene propylene ternary rubber, ceramic fiber modified polyisobutylene rubber, graphene oxide/hydrotalc composite filler, chopped basalt fiber, etc. are prepared through synergistic action to prepare anticorrosion rubber materials with good corrosion resistance and mechanical properties.

Benefits of technology

It significantly improves the corrosion resistance and mechanical properties of rubber materials, maintains good chemical stability under complex working conditions, and expands the application range of rubber materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of anti-corrosion rubber materials, in particular to an anti-corrosion rubber material and a preparation method and application thereof. The anti-corrosion rubber material is prepared from the following raw material components in parts by mass: 35 to 60 parts of urushiol acetal resin modified ethylene propylene diene monomer, 35 to 55 parts of ceramic fiber modified polyisobutene rubber, 20 to 30 parts of graphene oxide / hydrotalcite composite filler, 10 to 25 parts of chopped basalt fiber, 5 to 15 parts of adhesive, 1 to 5 parts of anti-aging agent, 1 to 3 parts of activating agent and 1 to 3 parts of vulcanizing aid. By utilizing the synergistic effect of all the raw material components, the anti-corrosion rubber material has good corrosion resistance and mechanical property, and the problem that the application range is limited due to the fact that a rubber lining material in the prior art is poor in anti-corrosion property is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-corrosion rubber materials, and in particular to an anti-corrosion rubber material and a preparation method and application thereof. Background Art

[0002] In chemical production, various reactors, storage tanks, pipelines and other equipment are often exposed to corrosive media such as strong acids, strong alkalis, organic solvents, etc. Anti-corrosion rubber materials such as natural rubber, chloroprene rubber and nitrile rubber can effectively protect equipment, prevent leakage and corrosion damage, and ensure the safety and stability of the production process. With the continuous advancement of industrial technology, the performance requirements for anti-corrosion rubber materials are getting higher and higher, and the research and development of rubber materials with higher chemical corrosion resistance has become a hot research topic.

[0003] Natural rubber has good elasticity and wear resistance, can withstand certain impacts, and has good flex resistance, but poor resistance to strong oxidants, organic chemicals, and oil media; hard rubber is brittle and has a limited range of use. Neoprene has good weather resistance and ozone resistance, good flame retardancy, and has a certain tolerance to oils and chemicals, but poor acid and alkali resistance, which affects the elasticity and flexibility of rubber, and thus affects the anti-corrosion properties of rubber materials. Nitrile rubber has excellent oil resistance, but its high temperature resistance and acid resistance are poor, and its application range is very limited.

[0004] Based on this, developing a rubber material with good anti-corrosion performance has great practical significance for the development of rubber lining materials. Summary of the invention

[0005] In view of the problem that the rubber lining material in the prior art has poor anti-corrosion performance and limited application scope, the present invention provides an anti-corrosion rubber material and its preparation method and application. The anti-corrosion rubber material includes raw material components such as lacquer phenol acetal resin modified EPDM rubber, ceramic fiber modified polyisobutylene rubber, graphene oxide / hydrotalcite composite filler, short chopped basalt fiber, adhesive, antioxidant, activator and vulcanization aid. By utilizing the synergistic effect of each raw material component, the anti-corrosion rubber material has good corrosion resistance and mechanical properties, and can maintain good chemical stability under complex working conditions, which provides a new idea for the preparation of rubber lining materials.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The first aspect of the present invention provides an anti-corrosion rubber material, which includes the following raw material components in parts by mass: 35-60 parts of phenol acetal resin modified ethylene propylene rubber, 35-65 parts of ceramic fiber modified polyisobutylene rubber, 10-20 parts of graphene oxide / hydrotalcite composite filler, 10-25 parts of chopped basalt fiber, 5-15 parts of adhesive, 1-5 parts of antioxidant, 1-3 parts of activator and 1-3 parts of vulcanization aid.

[0007] Compared with the prior art, the present invention designs a rubber material with excellent anti-corrosion performance, including raw material components such as lacquer phenol acetal resin modified EPDM rubber, ceramic fiber modified polyisobutylene rubber, graphene oxide / hydrotalcite composite filler, short chopped basalt fiber, adhesive, antioxidant, activator and vulcanization accelerator. Among them, the lacquer phenol acetal resin itself has good anti-corrosion performance, can effectively resist the corrosion of chemical substances such as acid, alkali and salt, and after combining with EPDM rubber, a continuous and dense protective film can be formed on the rubber surface, further preventing the corrosive medium from contacting the rubber material and reducing the possibility of corrosion. In addition, the elasticity and toughness of the rubber are combined with the hardness and strength of the lacquer phenol acetal resin, so that the mechanical properties such as tensile strength, tear strength and wear resistance of the lacquer phenol acetal resin modified EPDM rubber are improved. When subjected to external force, it has both the elastic deformation ability of the rubber and the anti-deformation ability brought by the resin, and is not easy to be damaged.

[0008] Polyisobutylene rubber itself has good chemical stability. Its molecular structure makes it tolerant to many chemical substances. When compounded with ceramic fiber, the ceramic fiber further enhances this tolerance. Rubber can provide a good bonding environment for ceramic fiber, so that the two can be closely combined and play a synergistic anti-corrosion role. When this composite structure is corroded by corrosive media, rubber can relieve the internal stress caused by the invasion of corrosive media through its own elastic deformation, reduce the material damage caused by stress concentration, and at the same time, the ceramic fiber enhances the corrosion resistance of the overall structure. More importantly, ceramic fiber has high strength and stability, forming an intricate network structure inside the rubber. When the corrosive medium (trying to invade the rubber, these ceramic fibers will hinder the penetration of the medium, slow down its diffusion rate, and make it difficult for the corrosive substances to contact the matrix inside the rubber, thereby reducing the occurrence of corrosion reactions; ceramic fiber can also adsorb and fix some ions in the corrosive medium, because the surface of ceramic fiber usually has a certain charge or active group. After these ions are adsorbed, the concentration of harmful ions in the corrosive medium is reduced, thereby reducing their corrosion to the rubber.

[0009] Graphene oxide has a two-dimensional lamellar structure, with the lamellar layers stacked and staggered, like tiles stacked one on top of the other. These lamellar structures can effectively block the contact of the surface of the corrosive medium material. Hydrotalcite also has a lamellar structure. The combination of the two can form a more complex and dense physical barrier, which greatly delays the penetration of corrosive substances. In addition, the surface of graphene oxide contains abundant oxygen-containing functional groups, such as hydroxyl and carboxyl groups, which can form chemical bonds with the metal surface, so that the composite material is firmly adsorbed on the metal surface. At the same time, these functional groups can react with the ions in the corrosive medium to play a role in corrosion inhibition. More importantly, the synergistic effect of graphene oxide and hydrotalcite can improve the self-healing ability of the material. When the surface covered by the composite material is partially damaged, graphene oxide and hydrotalcite can rearrange and fill to a certain extent, repair the damaged protective layer, and prevent the corrosive medium from continuing to corrode the matrix through the damaged area. The addition of short-cut basalt fibers can provide good mechanical strength and hardness for rubber materials.

[0010] In summary, the present invention utilizes the synergistic effect of each component to prepare a rubber material with good anti-corrosion performance, which effectively solves the problem of limited application range caused by poor anti-corrosion performance of rubber lining materials in the prior art, and provides a new idea for the preparation of rubber lining materials. Preferably, the preparation method of the lacquer phenol acetal resin modified EPDM rubber comprises the following steps: S1, kneading EPDM rubber at 60°C-70°C to obtain kneaded rubber; mixing the kneaded rubber and lacquer phenol acetal resin uniformly, and kneading at 90°C-120°C to obtain a mixture; S2, adding a vulcanizing agent and an activating agent to the mixture for vulcanization to obtain lacquer phenol acetal resin modified EPDM rubber.

[0011] Further preferably, in S1, the banburying time is 10 min-15 min.

[0012] Further preferably, in S1, the mass ratio of the EPDM rubber to the lacquer phenol acetal resin is 2:1-3:1.

[0013] Further preferably, in S1, the mixing speed is 80 rpm-120 rpm; and the mixing time is 20 min-25 min.

[0014] Further preferably, in S2, the vulcanizing agent is dicumyl peroxide; and the amount of the vulcanizing agent added is 5%-10% of the mass of the EPDM rubber.

[0015] Further preferably, in S2, the active agent is stearic acid, and the amount of the active agent added is 1%-2% of the mass of the EPDM rubber.

[0016] Further preferably, in S2, the vulcanization temperature is 140°C-180°C, the vulcanization pressure is 10MPa-20MPa, and the vulcanization time is 18h-22h.

[0017] Preferably, the preparation method of the ceramic fiber modified polyisobutylene rubber comprises the following steps: Step a, dispersing ceramic fibers in an alcohol solution of a silane coupling agent, performing ultrasonic treatment, standing, and performing solid-liquid separation to obtain pretreated ceramic fibers; Step b, refining the polyisobutylene rubber at 50° C.-75° C., adding the pretreated ceramic fiber, mixing at 90° C.-110° C., adding a vulcanizing agent for vulcanization, and obtaining ceramic fiber modified polyisobutylene rubber.

[0018] Further preferably, in step a, the temperature of the ultrasonic treatment is 40°C-45°C, and the time of the ultrasonic treatment is 1h-2h.

[0019] Further preferably, in step a, the mass volume ratio of the ceramic fiber to the alcohol solution of the silane coupling agent is 1 g:4 mL-1 g:6 mL.

[0020] Further preferably, in step a, the silane coupling agent is KH570 or KH550.

[0021] Further preferably, in step a, the mass percentage of the solute in the alcohol solution of the silane coupling agent is 65%-75%.

[0022] Further preferably, in step a, the standing time is 18h-24h.

[0023] Further preferably, in step b, the refining time is 8 min-12 min.

[0024] Further preferably, in step b, the mass ratio of the ceramic fiber to the polyisobutylene rubber is 1:5-1:8.

[0025] Further preferably, in step b, the mixing time is 10 min-15 min.

[0026] Further preferably, in step b, the vulcanizing agent is dicumyl peroxide, and the amount of the vulcanizing agent added is 4%-8% of the mass of the polyisobutylene rubber.

[0027] Further preferably, in step b, the vulcanization temperature is 150° C.-175° C., the vulcanization pressure is 10 MPa-20 MPa, and the vulcanization time is 16 h-24 h.

[0028] Preferably, the preparation method of the graphene oxide / hydrotalcite composite filler comprises the following steps: dispersing graphene oxide and hydrotalcite in deionized water respectively and performing ultrasonic treatment to obtain a graphene oxide suspension and a hydrotalcite suspension; mixing and stirring the graphene oxide suspension and the hydrotalcite suspension, allowing to settle, separating the solid from the liquid, drying, and grinding to obtain a graphene oxide / hydrotalcite composite filler.

[0029] Further preferably, the mass volume ratio of the graphene oxide to the deionized water is 1 g:1L-1.5 g:1L.

[0030] Further preferably, the mass volume ratio of the hydrotalcite to the deionized water is 1 g:1L-5 g:1L.

[0031] Further preferably, the mass ratio of the graphene oxide suspension to the hydrotalcite suspension is 1:2-1:3.

[0032] Further preferably, the drying temperature is 80° C.-100° C., and the drying time is 10 h-12 h.

[0033] Preferably, the antioxidant is antioxidant MB.

[0034] Preferably, the activator is stearic acid.

[0035] Preferably, the vulcanization aid is sulfur and ethylene thiourea in a mass ratio of 1:2.

[0036] Preferably, the adhesive is hexamethoxymethylmelamine.

[0037] The second aspect of the present invention provides a method for preparing the anti-corrosion rubber material, comprising the following steps: Step 1: weigh phenol acetal resin modified EPDM rubber and ceramic fiber modified polyisobutylene rubber according to the designed ratio, mix them evenly, and knead them at 85° C.-95° C. to obtain a mixed rubber; Step 2: Add the remaining components to the mixed rubber, mix evenly, vulcanize at 160° C.-180° C., and extrude to obtain an anti-corrosion rubber material.

[0038] Preferably, in step 1, the mixing time is 15 min-20 min.

[0039] Preferably, in step 2, the vulcanization adopts a step-by-step vulcanization process, including two vulcanizations, wherein the temperature of the first vulcanization is 160°C-170°C, the pressure of the first vulcanization is 15-20MPa, and the time of the first vulcanization is 12h-16h; the temperature of the second vulcanization is 170°C-180°C, the pressure of the second vulcanization is 10-20MPa, and the time of the second vulcanization is 14h-18h.

[0040] A third aspect of the present invention provides an application of the anti-corrosion rubber material or the anti-corrosion rubber material prepared by the method for preparing the anti-corrosion rubber material in the field of flame retardant materials. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1 This embodiment provides an anti-corrosion rubber material and a preparation method thereof, which specifically includes the following contents: The anti-corrosion rubber material includes the following raw material components in parts by mass: 55 parts of lacquer phenol acetal resin modified EPDM rubber, 50 parts of ceramic fiber modified polyisobutylene rubber, 15 parts of graphene oxide / hydrotalcite composite filler, 15 parts of chopped basalt fiber, 10 parts of hexamethoxymethyl melamine, 3 parts of antioxidant MB, 2 parts of stearic acid and 2 parts of vulcanization aid.

[0043] The method for preparing the anti-corrosion rubber material comprises the following steps: Step 1: weigh phenol acetal resin modified EPDM rubber and ceramic fiber modified polyisobutylene rubber according to the designed ratio, mix them evenly, and knead them at 90° C. for 18 minutes to obtain a mixed rubber; Step 2: Add the remaining components to the mixed rubber, mix evenly, perform the first vulcanization at 165° C. and 18 MPa for 14 h, then heat to 175° C. and 20 MPa for the second vulcanization for 16 h, and extrude to obtain the anti-corrosion rubber material.

[0044] The method for preparing the lacquer phenol acetal resin modified EPDM rubber comprises the following steps: S1, kneading 300g of EPDM rubber at 65°C for 12min to obtain a kneaded rubber; mixing the kneaded rubber and 100g of lacquer phenol acetal resin uniformly, and kneading at 100°C at a speed of 100rpm for 25min to obtain a mixture; S2. Add 20 g of dicumyl peroxide and 5 g of stearic acid to the mixture, mix well, and vulcanize at 160° C. and 15 MPa for 20 h to obtain lacquer phenol acetal resin modified EPDM rubber.

[0045] The preparation method of the ceramic fiber modified polyisobutylene rubber comprises the following steps: Step a, dispersing 100 g of ceramic fiber in 500 mL of KH570 alcohol solution, performing ultrasonic treatment at 40° C. for 1.5 h, standing for 22 h, and filtering to obtain pretreated ceramic fiber; wherein the mass percentage of the solute in the KH570 alcohol solution is 70%; Step b, 600g of polyisobutylene rubber is milled at 60°C for 10min, the pretreated ceramic fiber is added, and the mixture is mixed at 100°C for 12min, and 30g of diisopropylbenzene peroxide is added for vulcanization to obtain ceramic fiber modified polyisobutylene rubber.

[0046] The preparation method of the graphene oxide / hydrotalcite composite filler comprises the following steps: dispersing 5 g of graphene oxide and 5 g of hydrotalcite in 5 L of deionized water respectively and performing ultrasonic treatment to obtain a graphene oxide suspension and a hydrotalcite suspension; mixing the graphene oxide suspension and the hydrotalcite suspension in a mass ratio of 1:2.5, standing and settling, solid-liquid separation, drying at 85° C. for 12 h, and grinding to obtain a graphene oxide / hydrotalcite composite filler.

[0047] The vulcanization aid is sulfur and ethylene thiourea in a mass ratio of 1:1.

[0048] Example 2 This embodiment provides an anti-corrosion rubber material and a preparation method thereof, which specifically includes the following contents: The anti-corrosion rubber material includes the following raw material components in parts by mass: 40 parts of lacquer phenol acetal resin modified EPDM rubber, 60 parts of ceramic fiber modified polyisobutylene rubber, 10 parts of graphene oxide / hydrotalcite composite filler, 22 parts of chopped basalt fiber, 12 parts of hexamethoxymethyl melamine, 2 parts of antioxidant MB, 3 parts of stearic acid and 3 parts of vulcanization aid.

[0049] The method for preparing the anti-corrosion rubber material comprises the following steps: Step 1: weigh phenol acetal resin modified EPDM rubber and ceramic fiber modified polyisobutylene rubber according to the designed ratio, mix them evenly, and knead them at 90° C. for 18 minutes to obtain a mixed rubber; Step 2: Add the remaining components to the mixed rubber, mix evenly, perform the first vulcanization at 165° C. and 18 MPa for 14 h, then heat to 175° C. and 20 MPa for the second vulcanization for 16 h, and extrude to obtain the anti-corrosion rubber material.

[0050] The method for preparing the lacquer phenol acetal resin modified EPDM rubber comprises the following steps: S1, kneading 300g of EPDM rubber at 65°C for 12min to obtain a kneaded rubber; mixing the kneaded rubber and 100g of lacquer phenol acetal resin uniformly, and kneading at 100°C at a speed of 100rpm for 25min to obtain a mixture; S2. Add 20 g of dicumyl peroxide and 5 g of stearic acid to the mixture, mix well, and vulcanize at 160° C. and 15 MPa for 20 h to obtain lacquer phenol acetal resin modified EPDM rubber.

[0051] The preparation method of the ceramic fiber modified polyisobutylene rubber comprises the following steps: Step a, dispersing 100 g of ceramic fiber in 500 mL of KH570 alcohol solution, performing ultrasonic treatment at 40° C. for 1.5 h, standing for 22 h, and filtering to obtain pretreated ceramic fiber; wherein the mass percentage of the solute in the KH570 alcohol solution is 70%; Step b, 600g of polyisobutylene rubber is milled at 60°C for 10min, the pretreated ceramic fiber is added, and the mixture is mixed at 100°C for 12min, and 30g of diisopropylbenzene peroxide is added for vulcanization to obtain ceramic fiber modified polyisobutylene rubber.

[0052] The preparation method of the graphene oxide / hydrotalcite composite filler comprises the following steps: dispersing 5 g of graphene oxide and 5 g of hydrotalcite in 5 L of deionized water respectively and performing ultrasonic treatment to obtain a graphene oxide suspension and a hydrotalcite suspension; mixing the graphene oxide suspension and the hydrotalcite suspension in a mass ratio of 1:2.5, standing and settling, solid-liquid separation, drying at 85° C. for 12 h, and grinding to obtain a graphene oxide / hydrotalcite composite filler.

[0053] The vulcanization aid is sulfur and ethylene thiourea in a mass ratio of 1:1.

[0054] Example 3 This embodiment provides an anti-corrosion rubber material and a preparation method thereof, which specifically includes the following contents: The anti-corrosion rubber material includes the following raw material components in parts by mass: 60 parts of lacquer phenol acetal resin modified EPDM rubber, 40 parts of ceramic fiber modified polyisobutylene rubber, 20 parts of graphene oxide / hydrotalcite composite filler, 25 parts of chopped basalt fiber, 15 parts of hexamethoxymethyl melamine, 3 parts of antioxidant MB, 3 parts of stearic acid and 3 parts of vulcanization aid.

[0055] The method for preparing the anti-corrosion rubber material comprises the following steps: Step 1: weigh phenol acetal resin modified EPDM rubber and ceramic fiber modified polyisobutylene rubber according to the designed ratio, mix them evenly, and knead them at 90° C. for 18 minutes to obtain a mixed rubber; Step 2: Add the remaining components to the mixed rubber, mix evenly, perform the first vulcanization at 165° C. and 18 MPa for 14 h, then heat to 175° C. and 20 MPa for the second vulcanization for 16 h, and extrude to obtain the anti-corrosion rubber material.

[0056] The method for preparing the lacquer phenol acetal resin modified EPDM rubber comprises the following steps: S1, kneading 300g of EPDM rubber at 65°C for 12min to obtain a kneaded rubber; mixing the kneaded rubber and 100g of lacquer phenol acetal resin uniformly, and kneading at 100°C at a speed of 100rpm for 25min to obtain a mixture; S2. Add 20 g of dicumyl peroxide and 5 g of stearic acid to the mixture, mix well, and vulcanize at 160° C. and 15 MPa for 20 h to obtain lacquer phenol acetal resin modified EPDM rubber.

[0057] The preparation method of the ceramic fiber modified polyisobutylene rubber comprises the following steps: Step a, dispersing 100 g of ceramic fiber in 500 mL of KH570 alcohol solution, performing ultrasonic treatment at 40° C. for 1.5 h, standing for 22 h, and filtering to obtain pretreated ceramic fiber; wherein the mass percentage of the solute in the KH570 alcohol solution is 70%; Step b, 600g of polyisobutylene rubber is milled at 60°C for 10min, the pretreated ceramic fiber is added, and the mixture is mixed at 100°C for 12min, and 30g of diisopropylbenzene peroxide is added for vulcanization to obtain ceramic fiber modified polyisobutylene rubber.

[0058] The preparation method of the graphene oxide / hydrotalcite composite filler comprises the following steps: dispersing 5 g of graphene oxide and 5 g of hydrotalcite in 5 L of deionized water respectively and performing ultrasonic treatment to obtain a graphene oxide suspension and a hydrotalcite suspension; mixing the graphene oxide suspension and the hydrotalcite suspension in a mass ratio of 1:2.5, standing and settling, solid-liquid separation, drying at 85° C. for 12 h, and grinding to obtain a graphene oxide / hydrotalcite composite filler.

[0059] The vulcanization aid is sulfur and ethylene thiourea in a mass ratio of 1:1.

[0060] Comparative Example 1 This comparative example provides an anti-corrosion rubber material, which differs from Example 1 in that the phenol acetal resin modified EPDM rubber is replaced with an equal amount of phenol acetal resin modified butyl rubber, and other components and processes remain unchanged and will not be described again here.

[0061] The preparation method of the lacquer phenol acetal resin modified butyl rubber comprises the following steps: S1, kneading 300g of butyl rubber at 65°C for 12min to obtain kneaded rubber; mixing the kneaded rubber and 100g of lacquer phenol acetal resin evenly, and kneading at 100°C at a speed of 100rpm for 25min to obtain a mixture; S2. Add 20 g of dicumyl peroxide and 5 g of stearic acid to the mixture, mix well, and vulcanize at 160° C. and 15 MPa for 20 h to obtain phenol acetal resin modified butyl rubber.

[0062] Comparative Example 2 This comparative example provides an anti-corrosion rubber material, which differs from Example 1 in that the ceramic fiber modified polyisobutylene rubber is replaced with an equal amount of polyisobutylene rubber, and other components and processes remain unchanged and will not be described again here.

[0063] Comparative Example 3 This comparative example provides an anti-corrosion rubber material, which differs from Example 1 in that the graphene oxide / hydrotalcite composite filler is replaced with an equal amount of carbon nanotube / hydrotalcite composite filler, and other components and processes remain unchanged and will not be described again here.

[0064] The preparation method of the carbon nanotube / hydrotalcite composite filler comprises the following steps: 5 g of carbon nanotubes and 5 g of hydrotalcite were dispersed in 5 L of deionized water and subjected to ultrasonic treatment to obtain a carbon nanotube suspension and a hydrotalcite suspension; the carbon nanotube suspension and the hydrotalcite suspension were mixed and stirred in a mass ratio of 1:2.5, allowed to stand for precipitation, solid-liquid separation, dried at 85° C. for 12 h, and ground to obtain a carbon nanotube / hydrotalcite composite filler.

[0065] Comparative Example 4 This comparative example provides an anti-corrosion rubber material, which differs from Example 1 in that the chopped basalt fibers are replaced with an equal amount of carbon fibers, and other components and processes remain unchanged, which will not be described herein.

[0066] In order to further reflect the technical effect of the present invention, the present invention conducted the following tests on the anti-corrosion rubber materials obtained in Examples 1-3 and Comparative Examples 1-4: (1) Shore A hardness test according to GB / T531.1-2008; (2) Wear resistance test according to GB / T1689-2014; (3) Oil resistance test according to GB / T1690-2006; (4) Water quality condition working test: Each anti-corrosion rubber material was immersed in a pH range of 4.5-5.0, a solid content of 400g / L, and a flow rate of 900m 3 / h slurry, the test working time is 1000h, and the wear and corrosion of the rubber material is observed. The test results are shown in Table 1.

[0067] Table 1 Performance test results of various anti-corrosion rubber materials

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An anti-corrosion rubber material, characterized in that: The anti-corrosion rubber material comprises the following raw material components in parts by mass: 35-60 parts of lacquer phenol acetal resin modified EPDM rubber, 35-65 parts of ceramic fiber modified polyisobutylene rubber, 10-20 parts of graphene oxide / hydrotalcite composite filler, 10-25 parts of chopped basalt fiber, 5-15 parts of adhesive, 1-5 parts of antioxidant, 1-3 parts of activator and 1-3 parts of vulcanization aid.

2. The anticorrosive rubber material according to claim 1, characterized in that: The preparation method of the lacquer phenol acetal resin modified EPDM rubber comprises the following steps: S1, kneading EPDM rubber at 60° C.-70° C. to obtain kneaded rubber; uniformly mixing the kneaded rubber with lacquer phenol acetal resin, and kneading at 90° C.-120° C. to obtain a mixture; S2, adding a vulcanizing agent and an activating agent to the mixture for vulcanization to obtain lacquer phenol acetal resin modified EPDM rubber.

3. The anticorrosive rubber material according to claim 2, characterized in that: In S1, the mixing time is 10-15 min; and / or In S1, the mass ratio of the EPDM rubber to the lacquer phenol acetal resin is 2:1-3:1; and / or In S1, the mixing speed is 80-120 rpm; the mixing time is 20-25 min; and / or In S2, the vulcanizing agent is dicumyl peroxide; the amount of the vulcanizing agent added is 5%-10% of the mass of the EPDM rubber; and / or In S2, the active agent is stearic acid, and the amount of the active agent added is 1%-2% of the mass of the EPDM rubber; and / or In S2, the vulcanization temperature is 140-180°C, the vulcanization pressure is 10-20MPa, and the vulcanization time is 18-22h.

4. The anticorrosive rubber material according to claim 1, characterized in that: The preparation method of the ceramic fiber modified polyisobutylene rubber comprises the following steps: Step a, dispersing ceramic fibers in an alcohol solution of a silane coupling agent, performing ultrasonic treatment, standing, and performing solid-liquid separation to obtain pretreated ceramic fibers; Step b, refining the polyisobutylene rubber at 50° C.-75° C., adding the pretreated ceramic fiber, mixing at 90° C.-110° C., adding a vulcanizing agent for vulcanization, and obtaining ceramic fiber modified polyisobutylene rubber.

5. The anticorrosive rubber material according to claim 4, characterized in that: In step a, the mass volume ratio of the ceramic fiber to the alcohol solution of the silane coupling agent is 1g:4mL-1g:6mL, wherein the mass percentage of the solute in the alcohol solution of the silane coupling agent is 65%-75%; and / or In step a, the silane coupling agent is KH570 or KH550; and / or In step a, the standing time is 18-24 hours.

6. The anticorrosive rubber material according to claim 4, characterized in that: In step b, the refining time is 8 min-12 min; and / or In step b, the mass ratio of the ceramic fiber to the polyisobutylene rubber is 1:5-1:8; and / or In step b, the mixing time is 10 min-15 min; and / or In step b, the vulcanizing agent is dicumyl peroxide, and the amount of the vulcanizing agent added is 4%-8% of the mass of the polyisobutylene rubber; and / or In step b, the vulcanization temperature is 150-175° C., the vulcanization pressure is 10-20 MPa, and the vulcanization time is 16-24 h.

7. The anticorrosive rubber material according to claim 1, characterized in that: The preparation method of the graphene oxide / hydrotalcite composite filler comprises the following steps: dispersing graphene oxide and hydrotalcite in deionized water respectively and performing ultrasonic treatment to obtain graphene oxide suspension and hydrotalcite suspension; mixing the graphene oxide suspension and the hydrotalcite suspension evenly, allowing to settle, performing solid-liquid separation, drying, and grinding to obtain the graphene oxide / hydrotalcite composite filler.

8. The anticorrosive rubber material according to claim 7, characterized in that: The mass volume ratio of the graphene oxide to the deionized water is 1 g:1 L-1.5 g:1 L; and / or The mass volume ratio of the hydrotalcite to the deionized water is 1 g:1 L-5 g:1 L; and / or The mass ratio of the graphene oxide suspension to the hydrotalcite suspension is 1:2-1:

3.

9. A method for preparing the anticorrosive rubber material according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: weigh phenol acetal resin modified EPDM rubber and ceramic fiber modified polyisobutylene rubber according to the designed ratio, mix them evenly, and knead them at 85° C.-95° C. to obtain a mixed rubber; Step 2: Add the remaining components to the mixed rubber, mix evenly, vulcanize at 160° C.-180° C., and extrude to obtain an anti-corrosion rubber material.

10. Use of the anti-corrosion rubber material according to any one of claims 1 to 8 or the anti-corrosion rubber material prepared by the preparation method of the anti-corrosion rubber material according to claim 9 in the field of flame retardant materials.